Curvularia linata as bioherbicide for management of Xanthium strumarium L., an abnoxious weed - A Critical Evualation - Shukla, Manisha; Mishra, Manoj (Journal of Phytology, 2012)
Xanthium strumarium L. is an exotic plant responsible for several agricultural, environmental and health problems in India. Due to non-acceptability of conventional methods of control, the possibilities of its management through an indigenous strain of Curvularia lunata had been explored. In the present study, the organism was recovered in pure culture from the infected/infested parts of the weed, seedling and detached leaf bioassays were employed to evaluate the effect of different epidemiological factors on efficacy of mycoherbicidal agent. Significant effect on herbicidal potential of C. lunata was recorded when subjected to different conditions. Maximum efficacy of the pathogen was observed at 30°C, 80% RH, 2-3 leaves stage when sprayed @ of 4.5 x 105 Sp. /ml. The present study experimentally emphasizes on the development of Curvularia lunata as a mycoherbicide in the management of the weed, Xanthium strumarium L.